Gate-tunable diode and photovoltaic effect in an organic–2D layered material p–n junction. Issue 37 (3rd September 2015) - Vélez, Saül; Ciudad, David; Island, Joshua; Buscema, Michele; Txoperena, Oihana; Parui, Subir; Steele, Gary A.; Casanova, Fèlix; van der Zant, Herre S. J.; Castellanos-Gomez, Andres; Hueso, Luis E.
Abstract : A device based on the combination of an organic with an inorganic 2D layered material provides a hybrid p–n junction with gate-tunable diode rectification and photovoltaic effect. Abstract : The semiconducting p–n junction is a simple device structure with great relevance for electronic and optoelectronic applications. The successful integration of low-dimensional materials in electronic circuits has opened the way forward for producing gate-tunable p–n junctions. In that context, we present here an organic (Cu-phthalocyanine)–2D layered material (MoS2 ) hybrid p–n junction with both gate-tunable diode characteristics and photovoltaic effect. Our proof-of-principle devices show multifunctional properties with diode rectifying factors of up to 10 4, while under light exposure they exhibit photoresponse with a measured external quantum efficiency of ∼11%. As for their photovoltaic properties, we found open circuit voltages of up to 0.6 V and optical-to-electrical power conversion efficiency of 0.7%. The extended catalogue of known organic semiconductors and two-dimensional materials offer the prospect for tailoring the properties and the performance of the resulting devices, making organic–2D p–n junctions promising candidates for future technological applications.